Analysis of the Reorientation of the National Vocational Training Development Program - Farizal, Nur; Habibi, Nugroho (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
ILO found that only 59% of graduates from BLK at the level of UPTD and UPTP - which transformed into BPVP, could be absorbed by industries in 2022 due to the mismatch of competencies with the needs of the labor market. Therefore, the reorientation of the National Vocational Training Development Program is urgently needed to create skilled and competent human resources (HR) in line with the needs of industries and the labor markets. The purpose of this study is, to analyze the issues arising in the management of HR in vocational training institutions in creating skilled and competent HR, along the absorption of BLK graduates into companies/industries. This study uses a descriptive analysis method aimed at analyzing the management of HR in BLK. The results of the study indicate that BLK management has not yet adhered to standardized norms, the level of absorption of BLK graduates into companies/industries is still low, and there is a mismatch between the competencies of BLK graduates and the labor market. The implications of the study results for the Ministry of Manpower are: (1) refocusing training targets based on training needs analysis and national development priorities; (2) standardizing training programs considering the typology of BLK and the distribution of vocational training institutions; (3) identifying potential training needs and revitalizing training resources in vocational training institutions; (4) mainstreaming vocational training and apprenticeships by developing funding patterns and partnership programs between the government and the business/industrial sector, also the central and regional governments.